HIV patient and provider feedback on a telehealth collaborative care for depression intervention. Issue 3 (4th March 2017) - Drummond, Karen L.; Painter, Jacob T.; Curran, Geoffrey M.; Stanley, Regina; Gifford, Allen L.; Rodriguez-Barradas, Maria; Rimland, David; Monson, Thomas P.; Pyne, Jeffrey M.
ABSTRACT: In the HIV Translating Initiatives for Depression into Effective Solutions project, we conducted a randomized controlled effectiveness and implementation trial comparing depression collaborative care with enhanced usual care in Veterans Health Administration HIV clinics in the US. An offsite HIV depression care team including a psychiatrist, a depression care manager (DCM), and a clinical pharmacist provided collaborative care using a stepped-care model of treatment and made recommendations to providers through the electronic health record system. The DCM delivered care management to HIV patients through phone calls, performing routine assessments and providing counseling in self-management and problem-solving. The DCM documented all calls in each patient's electronic medical record. In this paper we present results from interviews conducted with patients and clinical staff in a multi-stage formative evaluation (FE). We conducted semi-structured FE interviews with 26 HIV patients and 30 clinical staff at the three participating sites during and after the trial period to gather their experiences and perspectives concerning the intervention components. Interviews were transcribed verbatim and analyzed using rapid content analysis techniques. Patients reported high satisfaction with the depression care manager (DCM) phone calls. Both HIV and mental health providers reported that the DCM's chart notes in the electronic health record were very helpful, and most felt that a dedicated DCM for HIV patients is ideal to meet patient needs. Sites encountered barriers to achieving and maintaining universal depression screening, but had greater success when such screening was incorporated into routine intake processes. FE results demonstrated that depression care management via telehealth from an offsite team is acceptable and helpful to both HIV patients and their providers. Given that a centralized offsite depression care team can deliver effective, cost-effective, cost-saving services for multiple HIV clinics in different locations with high patient and provider satisfaction, broad implementation should be considered.